2019
DOI: 10.1073/pnas.1913199116
|View full text |Cite
|
Sign up to set email alerts
|

Natural human genetic variation determines basal and inducible expression of PM20D1 , an obesity-associated gene

Abstract: PM20D1 is a candidate thermogenic enzyme in mouse fat, with its expression cold-induced and enriched in brown versus white adipocytes. Thiazolidinedione (TZD) antidiabetic drugs, which activate the peroxisome proliferator-activated receptor-γ (PPARγ) nuclear receptor, are potent stimuli for adipocyte browning yet fail to induce Pm20d1 expression in mouse adipocytes. In contrast, PM20D1 is one of the most strongly TZD-induced transcripts in human adipocytes, although not in cells from all individuals. Two putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
(62 reference statements)
3
33
0
1
Order By: Relevance
“…PM20D1 encodes an enzyme that catalyzes the synthesis of Nlipidated/N-fatty-acyl amino acids which function as endogenous uncouplers of mitochondrial respiration in a UCP1-independent manner [6]; it was expressed higher in DN brown adipocytes and rosiglitazone increased its the expression in both SC and DN adipocytes without influence of the FTO allele status. This specific effect of the PPARγ-agonist was observed in other studies as well [9,41].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…PM20D1 encodes an enzyme that catalyzes the synthesis of Nlipidated/N-fatty-acyl amino acids which function as endogenous uncouplers of mitochondrial respiration in a UCP1-independent manner [6]; it was expressed higher in DN brown adipocytes and rosiglitazone increased its the expression in both SC and DN adipocytes without influence of the FTO allele status. This specific effect of the PPARγ-agonist was observed in other studies as well [9,41].…”
Section: Resultssupporting
confidence: 85%
“…Among the upregulated browning genes outside of the PPAR pathway, CIDEA was listed by ProFAT and also found in the Group 1 genes above, similarly to PM20D1 which was strongly influenced by natural genetic variations in humans [41] and CPT1B which was essential for beta-oxydation of fatty acids. Gamma-butyrobetaine dioxygenase (BBOX1) catalyzes the formation of L-carnitine from gamma-butyrobetaine and has been reported to play a role in adipocyte browning [42].…”
Section: Shared Pparγ Mediated Gene Expression Patterns In Dn and Scmentioning
confidence: 95%
“…PM20D1 encodes an enzyme that catalyzes the synthesis of N-lipidated/N-fatty-acyl amino acids, which function as endogenous uncouplers of mitochondrial respiration in a UCP1-independent manner [6]; it was expressed higher in DN brown adipocytes and rosiglitazone increased its expression in both SC and DN adipocytes regardless of the FTO allele status. This specific effect of the PPARγ-agonist was observed in other studies as well [9,41].…”
Section: Discussionsupporting
confidence: 85%
“…We found that KLF11 was among the rosiglitazone upregulated genes ( Figure 5D) in either SC or DN adipocytes suggesting that it may be involved in the regulation of browning of neck area adipocytes. Among the upregulated browning genes outside of the PPAR pathway, CIDEA was listed by ProFAT and also found in the Group 1 genes above, similar to PM20D1, which was strongly influenced by natural genetic variations in humans [41] and CPT1B which was essential for beta-oxidation of fatty acids. Gamma-butyrobetaine dioxygenase (BBOX1) catalyzes the formation of L-carnitine from gamma-butyrobetaine and has been reported to play a role in adipocyte browning [42].…”
Section: Shared Pparγ Mediated Gene Expression Patterns In Dn and Scmentioning
confidence: 90%
“…Thus it is critical to understand how gene-by-environment interactions are contributing to metabolic dysfunction. Such interactions have been shown to underlie variation in obesity and diabetes risk [38], and many individual genes have been identified with natural variants in human populations affecting metabolic response to environmental perturbations [914]. Research in animal models, in particular mouse models, has been used to manipulate dietary intake and environment in order to better understand the gene-by-environment interactions most relevant to human metabolism [1519].…”
Section: Introductionmentioning
confidence: 99%